Bibliometric Analysis of Most Cited Articles on Transcatheter Aortic Valve Implantation - Doğan, Ali; Kahraman, Serkan; Sarılar, Mert; Mansuroğlu, Denyan (Cerrahpaşa Medical Journal, 2022)
Objective: Transcatheter aortic valve implantation has emerged as a promising therapy for the treatment of severe aortic stenosis. Bibliometric analysis can be performed in a specific field to obtain influential publications. We aimed to determine the most cited articles about transcatheter aortic valve implantation and the characteristics of these highly cited articles. Methods: A search for transcatheter aortic valve implantation or transcatheter aortic valve replacement was implemented on Web of Science. It resulted in 13 459 publications, and the list of top 100 articles was defined according to the number of citations. Results: Journal, author, country, organizing center, and publication year with most articles on the list were Journal of the American College of Cardiology, John G. Webb, USA, St. Paul Hospital, and 2012, respectively. Articles with funding had higher average citations per year than no funding articles (P = .005). Funding was divided into 2 groups as government or foundation and industrial (private) funding. It was indicated that no funding had lower average citation per year than industrial funding (P = .014). A significant relation was demonstrated between journal impact factor and either average or total citations obtained by articles along with total number of articles of journals (r = 0.553, P < .001; r = 0.421, P < .001; r = 0.710, P = .001, respectively). Conclusion: The study provides a comprehensive analysis of the top 100 articles related to transcatheter aortic valve implantation according to the number of citations. Prominent features of the articles on the list were also reviewed. Cite this article as: Doğan A, Kahraman S, Sarılar M, Mansuroglu D. Bibliometric analysis of most cited articles on transcatheter aortic valve implantation. Cerrahpaşa Med J. 2022;46(3):208-214.